Musculoskeletal Pain and Its Association with the Impact of Ergonomics among University Students Studying Online During the COVID-19 Pandemic. A Cross-Sectional Survey: Muscoskeletal Pain and Impact of Ergonomics during the COVID-19 Pandemic - Younas, Hadiqa; Shahid, Nayab; Hakim, Sammra; Khan, Aman Ullah; Kashif, Muhammad (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2025)
The lockdown, due to the coronavirus, led to a change in lifestyle and physical activity in students. A greater number of university students stayed at home and had to shift towards telework, which predisposed them to different musculoskeletal disorders due to the lack of proper ergonomics. Objectives: To determine the prevalence of musculoskeletal pain and its association with the impact of ergonomics among university students studying online during the COVID-19 pandemic. Methods: A cross-sectional study was carried out with a total of 584 eligible university students in Pakistan. A self-administered questionnaire was used, with section A containing demographic data. The Standardized Nordic Questionnaire was used to analyze MSK symptoms. SPSS version 22.0 was used to analyze results. Results: During COVID’19 prevalence of musculoskeletal pain was identiﬁed in the sample, with majority of female students (64.7%) reporting MSK pain and 25% male. Before covid-19 pandemic, participants suffered musculoskeletal pain in different regions of the body, where the most affected regions were the neck (14.4%), the shoulder (8.6%), and the lower back (5.1%). During covid-19 quarantine, this percentage increased up to 95%, where mostly affected areas were the neck (28.9%), shoulder (30.8%), wrist/hand (6.8%), and lower back (19.5%). Conclusions: There was a high prevalence of musculoskeletal pain among university students. A significant association was found between MSK pain and adverse working conditions, such as laptops with monitors too low, chairs without armrests, hard edges on desktop surfaces, and long static postures due to a lack of routine breaks.